MAYA ANGELOU: FROM STRUGGLE TO STRENGTH – A VOICE FOR LIBERATION - Dalavai, V. R. (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Maya Angelou is regarded as a seminal figure in American literature and civil rights activism, renowned for her profound impact on comprehending the African American experience, particularly among slave descendants. Her work, which includes autobiographies, poetry, and lectures, dives deeply into the fight against structural oppression while celebrating the tenacity and dignity of Black people. Born in the segregated South, Angelou's own history of trauma and quiet inspired her to become a forceful advocate for the voiceless. Her foundational book, I Know Why the Caged Bird Sings, not only documents her early upbringing, but also focuses on the larger struggle for identity and empowerment in the face of racism. Angelou's poetry, particularly "Still I Rise" and "Phenomenal Woman," is both a tribute to Black persistence and a celebration of Black womanhood. Through her activism and literature, Angelou paved the way for future generations to reclaim their stories and fight for justice. Her enduring legacy continues to inspire, reminding us of the indomitable strength of the human spirit and the transformative power of narrative in the pursuit of freedom.